Easily deployable, multi-functional low frequency FS radar network / Nur Emileen Abd Rashid … [et al.] - Abd Rashid, Nur Emileen; Othman, Kama Azura; Ismail Khan, Zuhani; Zakaria, Nor Ayu Zalina (Research Innovation Business Unit, 2014)
A wireless network of FSR sensors has been designed for situational awareness in ground operations. Its primary objectives are the detection, parameter estimation and automatic target classification of various ground target (personnel, vehicles) entering or crossing its coverage area. The system is able to provide monitoring in remote or even inaccessible areas and does not require manual installation of sensors. The sensors could be spread into random positions directly on the ground from a remotely operated moving platform such as UAV. It detects and recognizes ground targets entering the network of coverage area.